Qualitative impact of salinity, UV radiation and turbulence on leaching of organic plastic additives from four common plastics — A lab experiment. Issue 1 (15th January 2016) - Suhrhoff, Tim Jesper; Scholz-Böttcher, Barbara M.
Abstract: Four common consumer plastic samples (polyethylene, polystyrene, polyethylene terephthalate, polyvinylchloride) were studied to investigate the impact of physical parameters such as turbulence, salinity and UV irradiance on leaching behavior of selected plastic components. Polymers were exposed to two different salinities (i.e. 0 and 35 g/kg), UV radiation and turbulence. Additives (e.g. bisphenol A, phthalates, citrates, and Irgafos® 168 phosphate) and oligomers were detected in initial plastics and aqueous extracts. Identification and quantification was performed by GC–FID/MS. Bisphenol A and citrate based additives are leached easier compared to phthalates. The print highly contributed to the chemical burden of the analyzed polyethylene bag. The study underlines a positive relationship between turbulence and magnitude of leaching. Salinity had a minor impact that differs for each analyte. Global annual release of additives from assessed plastics into marine environments is estimated to be between 35 and 917 tons, of which most are derived from plasticized polyvinylchloride. Highlights: None of the analyzed consumer plastics (PE, PET, PS and PVC) was chemically inert. Leaching was observed in all cases. Turbulence strongly increases leaching of additives and PS oligomers. Salinity alone, or combined with UV, while having an impact for each individual analyte, did not show a distinct, general trend on additive release. Prints (here from PE) strongly contribute to the chemical burden of plastics. Estimated from resulting data, between 35 and 917 tons of additives are potentially leached into the oceans every year.